Comparative genomic survey of Bacillus cereus sensu stricto isolates from the dairy production chain in Brazil. Issue 3 (27th December 2017) - Rossi, Gabriel Augusto Marques; Silva, Higor Oliveira; Aguilar, Carlos Eduardo Gamero; Rochetti, Arina Lázaro; Pascoe, Ben; Méric, Guillaume; Mourkas, Evangelos; Hitchings, Matthew D; Mathias, Luis Antonio; de Azevedo Ruiz, Vera Letticie; Fukumasu, Heidge; Sheppard, Samuel K; et al.
Abstract: The genomes of 262 Bacillus cereus isolates were analyzed including 69 isolates sampled from equipment, raw milk and dairy products from Brazil. The population structure of isolates showed strains belonging to known phylogenetic groups II, III, IV, V and VI. Almost all the isolates obtained from dairy products belonged to group III. Investigation of specific alleles revealed high numbers of isolates carrying toxin-associated genes including cytK (53.62%), hblA (59.42%), hblC (44.93%), hblD (53.62%), nheA (84.06%), nheB (89.86%) and nheC (84.06%) with isolates belonging to groups IV and V having significant higher prevalence of hblACD and group IV of CytK genes. Strains from dairy products had significantly lower prevalence of CytK and hblACD genes compared to isolates from equipment and raw milk/bulk tanks. Genes related to sucrose metabolism were detected at higher frequency in isolates obtained from raw milk compared to strains from equipment and utensils. The population genomic analysis demonstrated the diversity of strains and variability of putative function among B. cereus group isolates in Brazilian dairy production, with large numbers of strains potentially able to cause foodborne illness. This detailed information will contribute to targeted interventions to reduce milk contamination and spoilage associated with B. cereus in Brazil. Abstract : The population genomic analysis demonstrated the diversity of strains and variability of putative function among Bacillus cereus group isolates in Brazilian dairy production chain.